The reduction of 18F-FDG uptake ability of tumor tissue after neoadjuvant chemoradiotherapy in locally advanced rectal cancer can effectively reflect the degree of tumor regression - Wu, Fengpeng; Zhang, Xiaoxiao; Yang, Congrong; Wang, Kanghua; Xiao, Linlin; Zhou, Chaoxi; Zhao, Xinming; Wang, Guiying (Frontiers in Oncology, 2022)
Purpose: To evaluate the predictive value of 18F-fluorodeoxyglucose positron emission tomography–computed tomography (18F-FDG PET-CT) imaging parameters for the response to neoadjuvant chemoradiotherapy (nCRT) in locally advanced rectal cancer (LARC). Materials and methods: From January 2016 to March 2020, 52 LARC patients who underwent 18F-FDG PET-CT scans within 1 week before and 8-9 weeks after nCRT, were enrolled in this study according to a pre-designed screening criteria. After total mesorectal excision (TME) surgery, we assessed tumor response to treatment and analyzed the correlation between imaging parameters obtained from two PET-CT scans and tumor regression status. Results: Tumor response assessment showed that 13 of 52 patients received good response (GR), including 9 cases with pathological complete regression (pCR) and 4 cases with near-pathological complete regression (near-pCR). We also found that the maximum standard uptake value after nCRT (post-SUVmax), the response index (RI), the mean standard uptake values after nCRT (post-SUVmean), and the ratio of tumor SUVmean to liver SUVmean after nCRT (post-Ratio), were correlated with GR and pCR. Among these parameters, post-SUVmax and RI had a near-strong correlation with pCR (rs= -0.58 and 0.59, respectively), and also had a strong correlation with GR (rs = -0.7 and 0.63, respectively). Further ROC analysis showed that post-SUVmax and RI had higher values in predicting whether patients could achieve GR and pCR after nCRT, and the area under the curve (AUC) of both were greater than 0.9. The positive predictive values (PPVs) and negative predictive values (NPVs) of post-SUVmax for GR were 80.01% and 97.3%, and for pCR were 66.68% and 97.5%, respectively. The PPVs and NPVs of the RI values for GR were 84.61% and 94.87%, and for pCR were 69.24% and 100%, respectively. Conclusion: For LARC patients, the analysis of imaging parameters such as post-SUVmax and RI, which can reflect the changes of 18F-FDG uptake capacity of tumor tissues before and after nCRT, is of great value for predicting the response of patients to neoadjuvant therapy and guiding the selection of subsequent treatment strategies.